1989
DOI: 10.1007/bf01407181
|View full text |Cite
|
Sign up to set email alerts
|

Experimental transplantation gliomas in the adult cat brain

Abstract: Tumours were produced in the adult cat brain by injection of the rapidly growing anaplastic rat glioma clone F98 in order to study their neuropathology, pathophysiology, regional biochemistry and magnetic reasonance imaging. We report here the neuropathological behaviour of cell suspensions in the basal ganglia and the left cerebral hemisphere one, two, three, four and six weeks after stereotactic implantation with respect to tumour growth, immunological tumour regression and alterations of the blood-brain bar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 30 publications
1
4
0
Order By: Relevance
“…The macroscopic tumor appearance, histopathology and immunohistochemistry of selected relevant tumor progression markers were monitored in U87 human glioblastoma cells xenografted into the brain of rats. In accordance with other reports, maximum progressive tumor growth was observed after 2 -3 weeks (Wechsler et al, 1989). According to the WHO classification of human brain tumors (Kleihues & Cavenee, 2000), the transplantation tumors demonstrated features of anaplastic astrocytic tumor (WHO grade III), but become increasingly similar to glioblastomas (WHO grade IV) in the second and third generations.…”
Section: U87 Human Glioblastoma Cell Xenografts In Rat Brains and On supporting
confidence: 90%
See 1 more Smart Citation
“…The macroscopic tumor appearance, histopathology and immunohistochemistry of selected relevant tumor progression markers were monitored in U87 human glioblastoma cells xenografted into the brain of rats. In accordance with other reports, maximum progressive tumor growth was observed after 2 -3 weeks (Wechsler et al, 1989). According to the WHO classification of human brain tumors (Kleihues & Cavenee, 2000), the transplantation tumors demonstrated features of anaplastic astrocytic tumor (WHO grade III), but become increasingly similar to glioblastomas (WHO grade IV) in the second and third generations.…”
Section: U87 Human Glioblastoma Cell Xenografts In Rat Brains and On supporting
confidence: 90%
“…The objective of experimental neuro-oncology is to contribute to a better understanding of human malignant brain tumors (Wechsler et al, 1989). To this end, the development of several animal models has provided specific clues about the formation of gliomas (Pilkington et al, 1997).…”
Section: The Animal Models For Experimental Studies Of Human Malignanmentioning
confidence: 99%
“…2 A very weak immunogenicity characterizes this line, with reports of successful short-term implantations in cat brains. 32 It is extremely stable in culture, with no morphological changes observed in over a hundred cell passages in our laboratory. Few treatment strategies have produced significant tumor regression when tested on this cell line after intracranial implantation in its syngeneic host, and only a few investigators have reported survival improvement using this model in preclinical therapeutic trials.…”
Section: Discussionmentioning
confidence: 91%
“…The reason for this may be that the authors (often concentrating on oncological aspects) did not look for such signs, and indeed overlooked them since in many cases, even if seizure-like activity is being observed in the EEG, behavioural signs are often quite subtle, comprising freezing, facial automatisms and head tremor, or massive startle response in reaction to audiogenic stimuli, and only very seldom generalised tonic-clonic convulsions (Buckingham et al, 2011;Campbell et al, 2015;Köhling et al, 2006). Another reason may be that tumour cell injection into areas other than the neocortex such as capsula interna, corpus striatum or even cerebellar subdural space, are probably not ideal for the purpose of an epilepsy model (Aas et al, 1995;Beaumont et al, 1996;Hossmann et al, 1989;Krajewski et al, 1986;Linn et al, 1989;Rewers et al, 1990;Wechsler et al, 1989). Another problem is also revealed in Table 1.…”
Section: Methodological Aspectsmentioning
confidence: 95%